The Russian Counterparts of Italian Periphrases with Aspectual Value - Francesca Biagini; Lucyna Gebert (Studi Slavistici)
This contribution focuses on the realization in Russian of certain Italian aspectual periphrases – (in)cominciare/iniziare a, continuare a, cercare/tentare di using data from the Russian-Italian parallel corpus of the National Corpus of the Russian Language (nkrja). The theoretical framework adopted is based on the idea that the choice of aspectual forms in Slavic languages is determined by the lexical or actional classes of verbs: the natural, prototypical forms of telic verbs (achievements and accomplishments) are perfective, whereas those of atelic verbs (states and activities) are imperfective. Conversely, the forms of the opposite aspect activated for each class represent marked, peripheral choices with respect to the prototype. The comparison of the Italian periphrases with equivalent Russian verbal forms extracted from the corpus shows that they often correspond to simple aspectual forms in Russian, which quite systematically represent peripheral aspectual choices. As a result, Italian periphrases corresponding to Russian marked aspectual forms explicitly convey the additional semantic load that differentiates them from their unmarked, prototypical counterparts. Since Russian aspectual forms are synthetic and polysemous, the presence of periphrases with the hypothesized semantic value in Italian supports the validity of the adopted theoretical framework.